EFFECT OF DIFFERENT COOKING METHODS ON THE CHARACTERISTICS OF CLIMBING PERCH (Anabas testudineus)MEAL - Imam Gusdika Rahman; Mery Sukmiwati; Dahlia ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research aimed to determine the chemical characteristics of climbing perch with different cooking methods in the making fish meal. The experiment was conducted in July and August 2015. This research used the experiment method. Cooking methods used in this research T0 (control), T1 (boiling) and T2 (steaming). Proximate analysis of three samples were tested by the soxhlet method and kjeldahl method. The average value proximate fish meal and cooking methods etching with T0, T1 and T2 are respectively the water content of 8.43%, 7.24% and 6.34%, ash content of 31.11%, 23.1% and 21 , 51%, protein content of 60.42%, 56.03% and 57.64%, fat 20.56%, 10.28% and 12.43% and crude fiber 3.5%, 2.4% and 2.1%. Keywords: fish meal, climbing perch, cooking methods,